2021
DOI: 10.3389/fmed.2021.622087
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Live Birth Rate Following Fresh Embryo Transfer Cycles in Infertile Women After Endometrioma Cystectomy

Abstract: Background: Reproductive outcomes after fresh in vitro fertilization/intracytoplasmic sperm injection–embryo transfer (IVF/ICSI–ET) cycles are diverse in infertile women with a history of ovarian cystectomy for endometriomas. We aimed to develop a logistic regression model based on patients' characteristics including number of embryos transferred and stimulation protocols to predict the live birth rate in fresh IVF/ICSI–ET cycles for such patients.Methods: We recruited 513 infertile women with a history of ova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Age < 35, AFC > 7 and having two embryos transferred may be associated with better outcome in fresh embryo transfer following IVF/ICSI in women who had previously undergone OMA cystectomy [ 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…Age < 35, AFC > 7 and having two embryos transferred may be associated with better outcome in fresh embryo transfer following IVF/ICSI in women who had previously undergone OMA cystectomy [ 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were no signi cant differences between the two groups in Gn duration, E 2 levels on the trigger day, number of oocyte retrieval and sperm source of transplanted embryos. The selection of relevant predictive factors and cut-off values of the two groups was based on previously published articles (9) and the diagnosis and treatment standards of our center. As for the selection of cut-off BMI value, we referred to the BMI range recommended by Chinese experts for Chinese people (18.5-23.9 is normal, <18.5 is too low, and≥24 is overweight or obesity).…”
Section: Controlled Ovarian Stimulation and Ivf/icsi Characteristicsmentioning
confidence: 99%
“…A study showed that pregnancy pattern, age, and number of tubal ostia seen on second-look hysteroscopy affect live birth rates [6]. Other studies have also shown that age, body mass index, and lifestyle factors [7][8][9]. There has never been a study in Aceh Province that examines Maternal and Child Healthcare Services factors associated with birth rates seen through the service system and maps them in the form of maps in Aceh Province.…”
Section: Introductionmentioning
confidence: 99%